Prisoners' Educational Experiences in Five Different Prison Sports Programmes: A Research Note - Johannes Müller; Rosie Meek; Jonna Blessing; Michael Mutz (MDPI AG, 2023)
Organized sports programmes offer manifold opportunities for learning and personal development. Prisoners in organized sports programmes could profit from these educational opportunities, which could eventually support their process of reintegration into society. However, research on the educational experiences of imprisoned individuals during organized sports activities is scarce. Using quantitative survey data (N = 568 adult male prisoners) collected within the scope of the Hessian Prison Sports Study in Hesse, Germany, the present study examines educational experiences that are instigated through participation in five different prison sports programmes (fitness, racket, and team sports, running groups, and strength training). The results show that participants reported few educational experiences. The most common experiences reported were learning to exert effort and acquiring health-related knowledge. The findings reveal distinct patterns for specific sports programmes. For instance, team sports more frequently address cooperation skills and fairness. This paper advocates for more attention to the educational potential of sports in prison settings, where sports outcomes should be better aligned with the desired educational outcomes.